Effect of polydispersity on the bulk‐heterojunction morphology of P3HT:PCBM solar cells. Issue 14 (1st July 2019) - Munshi, Joydeep; Ghumman, Umar Farooq; Iyer, Akshay; Dulal, Rabindra; Chen, Wei; Chien, TeYu; Balasubramanian, Ganesh
ABSTRACT: Bulk heterojunctions (BHJs) based on semiconducting electron–donor polymer and electron–acceptor fullerene have been extensively investigated as potential photoactive layers for organic solar cells (OSCs). In the experimental studies, poly‐(3‐hexyl‐thiophene) (P3HT) polymers are hardly monodisperse as the synthesis of highly monodisperse polymer mixture is a near impossible task to achieve. However, the majority of the computational efforts on P3HT: phenyl‐C61‐butyric acid methyl ester (P3HT:PCBM)‐based OSCs, a monodisperse P3HT is usually considered. Here, results from coarse‐grained molecular dynamics simulations of solvent evaporation and thermal annealing process of the BHJ are shared describing the effect of variability in molecular weight (also known as polydispersity) on the morphology of the active layer. Results affirm that polydispersity is beneficial for charge separation as the interfacial area is observed to increase with higher dispersity. Calculations of percolation and orientation tensors, on the other hand, reveal that a certain polydispersity index ranging between 1.05 and 1.10 should be maintained for optimal charge transport. Most importantly, these results point out that the consideration of polydispersity should be considered in computational studies of polymer‐based OSCs. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 895–903 Abstract : The effect of polydispersity of poly‐(3‐hexyl‐thiophene) molecules, used in conjunction with phenyl‐C61‐butyric acid methyl ester for bulk heterojunction‐based organic solar cells, on the blend morphology is examined. Polydispersity index between 1.05 and 1.10 is found to be optimum based on calculation of orientation tensor, percolation ratio, and interfacial area to volume ratio. Simulations reveal that polydispersity is an important design variable to be considered for optimizing power conversion efficiency of organic photovoltaics.